The role of instruments in the dissemination of the Chemical Revolution - Levere, Trevor H. (ENDOXA, 2005)
The spread of the late eighteenth-century chemical revolution depended on access to appropriate apparatus. Theories depend upon practice, which depends upon instruments. Pneumatic chemistry required new apparatus for the isolation, measurement, and admixture of difFerent gases. Lavoisier's pneumatic chemistry invoived his new, refined, expensive gasometers. The development of cheaper but still fimctional gasometers by chemists and instrument makers enabled chemists outside Paris to repeat and extend Lavoisier's key experiments. Lavoisier's superb precisión balances were an important part of his arsenal. Glass apparatus made increasing demands on glass blowers. The bottle faetones that had supplied Black in Edinburgh and later Proust in Segovia were no longer adequate.